Influence and persuasion : emotional intelligence - Harvard Business Review (Boston Harvard Business Review, 2017)
Changing hearts is an important part of changing minds. Research shows that appealing to human emotion can help you make your case and build your authority as a leader.This book highlights that research and shows you how to act on it, presenting both comprehensive frameworks for developing influence and small, simple tactics you can use to convince others every day.This volume includes the work of:Nick MorganRobert CialdiniLinda A. HillNancy DuarteThis collection of articles includes Understand the Four Components of Influence, by Nick Morgan; Harnessing the Science of Persuasion, by Robert Cialdini; Three Things Managers Should Be Doing Every Day, by Linda A. Hill and Kent Lineback; Learning Charisma, by John Antonakis, Marika Fenley and Sue Liechti; To Win People Over, Speak to Their Wants and Needs, by Nancy Duarte; Storytelling That Moves People, an interview with Robert McKee by Bronwyn Fryer; The Surprising Persuasiveness of a Sticky Note, by Kevin Hogan; and When to Sell with Facts and Figures and When to Appeal to Emotions, by Michael D. Harris.How to be human at work. The HBR Emotional Intelligence Series features smart, essential reading on the human side of professional life from the pages of Harvard Business Review. Each book in the series offers proven research showing how our emotions impact our work lives, practical advice for managing difficult people and situations and inspiring essays on what it means to tend to our emotional well-being at work. Uplifting and practical, these books describe the social skills that are critical for ambitious professionals to master.
Keywords: Persuasion (Psychology) -- Work--Psychological aspects